2020
DOI: 10.1142/s021951942040028x
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Hand Gesture Classification Using CRNN With Scale Average Wavelet Transform

Abstract: It is very useful in the human computer interface to quickly and accurately recognize human hand movements in real time. In this paper, we aimed to robustly recognize hand gestures in real time using Convolutional Recurrent Neural Network (CRNN) with pre-processing and overlapping window. The CRNN is a deep learning model that combines Long Short-Term Memory (LSTM) for time-series information classification and Convolutional Neural Network (CNN) for feature extraction. The sensor for hand gesture detection use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The FFNN, LSTM, RNN, and GRU models exhibited equivalent accuracy, 95% for the DualMyo dataset and 91% for the NinaPro DB5 dataset. Jo et al [48] suggested Convolutional Recurrent Neural Network (CRNN) model to recognize hand motions in real time by combining LSTM for time-series information classification and CNN for feature extraction. Two grips, three hand signals, and one rest are recognized and categorised as hand gestures.…”
Section: Review Of Related Approachesmentioning
confidence: 99%
“…The FFNN, LSTM, RNN, and GRU models exhibited equivalent accuracy, 95% for the DualMyo dataset and 91% for the NinaPro DB5 dataset. Jo et al [48] suggested Convolutional Recurrent Neural Network (CRNN) model to recognize hand motions in real time by combining LSTM for time-series information classification and CNN for feature extraction. Two grips, three hand signals, and one rest are recognized and categorised as hand gestures.…”
Section: Review Of Related Approachesmentioning
confidence: 99%
“…The dataset EMG signals similar to five diverse gestures are formed as part of the study. In Jo and Oh (2020), the authors aimed to vigorously detect hand gestures in real time by employing CRNN with overlapping windows and preprocessing. CRNN is a deep learning method that incorporates LSTM for time-sequence data classification and CNN for feature extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The sEMG signal is an unstable bioelectric signal with different frequency components at different moments [ 24 ]. The representative time-frequency analysis methods of the sEMG signal include fast Fourier transform (FFT) [ 25 ], short-term Fourier transform (STFT) [ 26 , 27 ], Wigner–Ville distribution (WVD) [ 28 , 29 ] and Hilbert–Huang transform (HHT) [ 30 ], and wavelet transform (WT) [ 18 , 31 , 32 ]. The prerequisite for FFT and STFT to effectively analyze the signal is that the signal is stable [ 33 ].…”
Section: Introductionmentioning
confidence: 99%